Service-Learning for the acquisition of musical skills in future teachers: Service-Learning for the acquisition of musical skills in future teachers - Arroyo Resino, Delia; Bonastre Vallés, Carolina; Cuervo Calvo, Laura; García Gil, Desiree; Camilli Trujillo, Celia (Revista Complutense de Educación, 2026)
Service Learning (SL) is a learning strategy characterised by the fact that participants provide a service to the community and simultaneously learn curricular content. Based on this, the aim of this work was to evaluate the effectiveness of SL in future teachers during the experience, and the enhancement of musical competences. A quantitative design, quasi-experimental, pretest-posttest without a control group was carried out, in addition to a qualitative approach. The total sample consisted of 52 students from the Double Degree in Early Childhood Education and Pedagogy, selected by non-probabilistic sampling, by accessibility. The information was collected by a questionnaire which measured competences related with Music Education of future Early Childhood Education teachers, and a self-assessment of the SL experience. Furthermore, the reflective records consisting of questions related to different moments of the experience. Significant differences were found in all items of the competency questionnaire, between pre and post, in favour of post, with medium and large effect sizes, and both self-assessment and reflective records reaffirmed the effectiveness of the service. This research shows the multidimensional impact of SL in the university context regarding improved musical learning, but also enhanced teaching competence, professional identity and personal development of the students.
Keywords: service learning; music education; teaching competences; preservice teachers; concurrent triangulation mixed design